P-B6 Development of a Potency Assay for Full Length Single Chain, a subunit vaccine for HIV. (January 2016) - Prado, Ilia; Schwartz, Jennifer; Xu, Rong; Lewis, George; Fouts, Timothy; Devico, Anthony
Abstract : Antibodies that recognize highly conserved domains on envelope could inhibit HIV infection by direct neutralization or by Fc receptor-dependent effector mechanisms including ADCC. The Full Length Single Chain (FLSC) is a gp120-CD4 D1D2 fusion that stably expresses a highly conserved transition state structure that is exposed on gp120 after it engages CD4, and is antigenically distinct from free gp120 or the trimeric envelope. This transitional structure can be defined by monoclonal antibodies such as N12-i2 that recognize CD4 induced epitopes. We exploited this aspect to develop a potency assay based on the binding of N12-i2 to the FLSC subunit that could be used for in process and release testing during cGMP manufacture as well as to assess long term stability of drug substance and drug product. Antibody responses that competed with N12-i2 correlated with protection in "proof-of-concept" studies in rhesus macaques that used both the single high dose and multiple low dose SHIV challenge models. Competitive titers to N12-i2 correlated with the dose of FLSC administered in two separate rabbit studies. The first used increasing doses of FLSC formulated in Alum. The second, used varying ratios of FLSC/gp120 also formulated in Alum. In both cases, the competitive titers to N12-i2 also correlated with antibody titers to FLSC but not gp120. Additional experiments were performed to determine the specificity, linearity, LLOQ, reproducibility, etc in order to qualify the assay. Based on these results, binding of CD4i antibody N12-i2 to FLSC was selected to be the principle measure of potency for the FLSC vaccine.